Development of Scrabble CTPS as a Health Promotion Media for Elementary School Students in Malang - Samara, Rufaidah As; Adi, Sapto; Ratih, Suci Puspita (JHE (Journal of Health Education), 2021)
Background: Acute Respiratory Infections (ARI) are often suffered by the child's age group. In 2018, the prevalence of national-scale ISPA decreased. Nevertheless, the prevalence of ISPA in Malang continues to increase and always ranks first in diseases with the highest prevalence compared to other diseases. The prevalence of ISPA in Malang in 2018 increased by 19.273 cases from the prevalence in 2013. Air pollution such as cigarette smoke and poor health behaviors such as wrong hand washing are the main causes of ISPA. Not only ISPA, wrong hand washing behavior can also cause a variety of other health problems. Therefore, education is needed related to the prevention of ISPA, especially related to CTPS (Cuci Tangan Pakai Sabun/Hand Washing with Soap) in children, by using effective media used as educational aids, such as scrabble. Method: The development method uses modifications from the Sugiyono development method (2013). Media validation was conducted by three experts and trials were conducted to two different target groups. The interventions given to the target are scrabble CTPS and assessment sheet filling. Result: Scrabble CTPS validation by public health experts gets 80% results, validation by media development experts gets 85% results, and validation by classroom teachers gets 96.92% results. While the calculation of trial scoring in small groups obtained results of 100% and trials in large groups obtained results of 98,31%. Conclusion: Scrabble CTPS are well worth using as a health promotion media for Hand Washing with Soap (CTPS) in elementary school students, especially in Grade V students. KEY WORDS: ARI; CTPS; scrabble